The occurrence of code-switching in English as foreign language Classroom: An analysis of teacher’s and students’ conversations - Rinda, Renata Kenanga (Journal of English Language Teaching and Learning (JETLE), 2024)
Code-switching is an exciting phenomenon in the English classroom, especially in multilingual settings. While it is being practiced, several types of it have appeared. Dealing with the previous phenomenon, this research is intended to describe the types of code-switching used by the English teacher while conducting English classrooms. Descriptive research was used as the framework of this study to cope with the earlier goal. In collecting the data, the audio recording was used to record the classroom conversation and then transcribed into written form. After that, the data was analyzed. Furthermore, the findings highlight that the teacher uses three types of code-switching: tag-switching, inter-sentential switching, and intra-sentential switching. Also, this study reclassified the tag-switching into tag-switching with tag-phrase at the initial and the end of the sentence. Then, it regrouped inter-sentential switching into inter-sentential switching between clause and sentence and inter-sentential switching between two sentences. Last, it recategorized intra-sentential switching into intra-sentential switching with embedded words and intra-sentential switching with the inserted words. By describing the previous findings, it is hoped that types of code-switching can be clearly understood.